Road traffic injury risk from alcohol and cannabis use among emergency department patients in Argentina - Karina Conde; Raquel Inés Peltzer; Paula Victoria Gimenez; Tomás Salomón; Gabriel Suarez; Maristela Monteiro; Cheryl J Cherpitel; Mariana Cremonte (Pan American Health Organization, 2022)
Objective. To report the risk from alcohol, cannabis, and their combined use for non-fatal road traffic injuries for drivers, passengers, and pedestrians. Methods. Risk was estimated using the case-crossover method. Participants (N= 306) were injured patients from an emergency department in Mar del Plata, Argentina. Results. Alcohol use (OR= 6.78, CI 95% 3.75-12.25) as well as combined alcohol and cannabis use (OR= 7.05, CI 95% 1.16-42.73) significantly increased the risk of a road traffic injuries. Alcohol use increased the risk in both, women (OR= 8.87, CI 95% 2.69-29.21) and men (OR= 6.16, CI 95% 3.10-12.23); in those >30 years old (OR= 6.01, CI 95% 2.09-17.24) and those <30 years old (OR= 7.15, CI 95% 3.49-14.65). This last group also had an increased risk after combined alcohol and cannabis use (OR= 7.05, CI 95% 1.16-42.75). Both drivers (OR= 6.40, CI 95% 3.23-12.69) and passengers (OR= 13.83, CI 95% 2.87-66.42) had an increased risk after alcohol consumption. Conclusions. To our knowledge, these are the first estimates of the risk of having a road traffic injury after alcohol and cannabis consumption in one of the countries of the Southern Cone (Argentina, Chile, and Uruguay). These results highlight the urgent need to implement and enforce comprehensive alcohol control measures. Furthermore, given the global trend towards legalizing cannabis for recreational use, our results could also inform policymakers to enact or amend impaired driving laws.